Assessment and Recommendations for Enhancing Compliance in Income Tax Article 21 Calculations: A Case Study of XYZ Hospital - Priyanti, Utari; Aisyah, Siti (Jurnal Ilmiah Manajemen Kesatuan, 2023)
XYZ Hospital, situated in Medan City, North Sumatra Province, is a private healthcare facility established with the vision of delivering exceptional services to fulfill the health requirements of the community. In the context of compensating specialist doctors, XYZ Hospital employs the PPh Article 21 calculations. This study seeks to assess and analyze whether XYZ Hospital in Medan has accurately executed PPh Article 21 calculations and to identify the challenges encountered in this process. Data collection involved interviews with XYZ Hospital in Medan, utilizing NVivo software and a framework of matrices for analysis. The findings indicate that the computation of Income Tax Article conducted by XYZ Hospital in Medan deviates from the stipulated legal rate of 5%. Identified obstacles include a lack of precision in the financial department’s calculations. Additionally, XYZ Hospital in Medan has implemented efforts to enhance its understanding of taxation and to adhere to applicable tax regulations.